Blended learning as a pedagogical framework for developing e-marketing literacy and applied skills among secondary school English language students - Saleh, Shoeb; Elsayed Hassan, Eid Awad Abd; Kegour, Adam Basheer Adam; Masha, Anees Abdulatif; Koka, Nisar Ahmad; Alomari, Mohammad Ahmad Shehadeh (Research Journal in Advanced Humanities, 2026)
The study aimed to investigate the effectiveness of the blended learning strategy in developing the concepts and skills of e-marketing among female students in the first grade of commercial secondary school. The intervention of study was administrated to a sample of (40) female students at Tema E- Educational Commercial Secondary School, using a test of cognitive achievement to measure the conceptual aspect, and a card to evaluate the outcome to measure performance skills. A comprehensive list was developed that included (30) concepts and (4) main skills subdivided into (24) sub-skills, all of which were implemented within the framework of a blended learning environment designed according to design models Educational. The results showed the effectiveness of strategy in improving cognitive achievement and developing practical skills, in addition to enhancing interaction and motivation towards learning, which reflects the feasibility of employing blended learning environments in technical and commercial education, and it is consistent with the results of previous studies that confirmed its positive effect on improving achievement and skills development.